Machiavellianism, Social Responsibility, Fairness, and Tax Avoidance - Lisa Arisa; Imam Abu Hanifah (JURNAL RISET AKUNTANSI TIRTAYASA, 2022)
This study aims to examine the influence of machiavellianism, social responsibility, fairness, tax Administration, tax knowledge toward tax avoidance in Banten. The population in this study are all of manufacturing companies in Banten with finance accounting manager and tax supervisor as unit analyzed. Sample in this study are finance accounting manager and tax supervisor who worked in manufacuring companies have operated more than three years and willing to become respondent in this study. This study uses purposive sampling as sampling method. Data in this study taken by spreading questionnaires directly to the respondents. From 108 questioner which send directly to respondent. They are 75 questioners that can proceed. Data in this study analyzed by using multiple regression. Data proceeds by using SPSS version 20 software. The result of this study reveals that machiavellianism, fairness, tax administrations, knowledge of tax are significat influence tax avoidance. Meanwhile social responsibility insignificant influence the tax avoidance.